2013
DOI: 10.4314/rjhs.v2i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Cervical Traction in the Management of Cervical Radiculopathy: A Control Trial

Abstract: Background: Severe pain and disability from cervical disorder is second to that of low back pain in musculoskeletal practice. Methods: Forty eight patients who met the inclusion criteria were placed into experimental (n=24) and control (n=24) group randomly. Participants in both groups received massage, cryotherapy and active exercises. Cervical traction was administered to experimental group for 15 minutes, thrice per week for four weeks while the other group served as control. Verbal rating scale (VRS) and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
(24 reference statements)
1
3
0
Order By: Relevance
“…Mechanical cervical traction was also found to produce significant reduction in pain intensity in this study, this was in accordance with study conducted by Cleland, et al, Ojoawo, et al and Abid, et al, where MCT produced significant reduction in pain intensity in cervical radiculopathy and improvement on neck disability [10,28,29]. The significant reduction observed was due to decrease in radicular symptoms.…”
Section: Comparisons Between the Effects Of Snags And Mct On Pre-treatment 3 Rd And 6 Th Weeks Treatment Of Pain Intensity (Pi) And Neck supporting
confidence: 91%
See 2 more Smart Citations
“…Mechanical cervical traction was also found to produce significant reduction in pain intensity in this study, this was in accordance with study conducted by Cleland, et al, Ojoawo, et al and Abid, et al, where MCT produced significant reduction in pain intensity in cervical radiculopathy and improvement on neck disability [10,28,29]. The significant reduction observed was due to decrease in radicular symptoms.…”
Section: Comparisons Between the Effects Of Snags And Mct On Pre-treatment 3 Rd And 6 Th Weeks Treatment Of Pain Intensity (Pi) And Neck supporting
confidence: 91%
“…A study by Ojoawo, et al, on the therapeutic efficacy of cervical traction in the management of cervical radiculopathy; a significant improvement in the pretreatment and post-treatment pain intensity and neck functional disability of participants in experimental group, and a significant difference in the post-treatment pain intensity between the cervical traction and control group were reported [10]. Thus, both SNAGS and MCT have been reported to effect changes in the symptoms and disabilities accompanying cervical radiculopathy [9,10]. This study was designed to explore the effects of SNAGS and MCT on cervical radiculopathy to determine which one is more effective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review by Graham et al 27 also reported that there was moderate evidence to support the use of mechanical intermittent CT in the management of cervical disorder. Ojoawo et al 28 in their study reported that CT is effective in the management of CR. CT in addition to other exercises is the major treatment technique in many facilities in Nigeria physiotherapy clinic to manage CR but there are paucity of data on its efficacy in Nigerian environment.…”
Section: Introductionmentioning
confidence: 97%